(untitled) (South Asian Journal of Agriculture, 2026)
Despite significant progress, women in rural Bangladesh continue to face systemic socioeconomic and cultural barriers to empowerment, and there is a critical knowledge gap in understanding the interplay of these factors and the effectiveness of targeted interventions to overcome these challenges. This study examines the socioeconomic and cultural factors influencing women’s empowerment in rural Bangladesh, focusing on age, education, marital status, income sources, and societal norms. Data from purposively selected 120 respondents revealed that 61.7% were middle-aged, 49.2% had secondary education, and 83.3% lacked personal income, reflecting financial dependency. Key barriers included societal attitudes, racial discrimination (89.2%), mental misbehavior (83%), and domestic violence. Illiteracy emerged as the most critical challenge (severity index: 82.2%), followed by poverty (76.4%), and violence (70.8%). Educational attainment was positively correlated with empowerment, decision-making, and satisfaction, although highly educated women faced household exclusion. Women who engaged in income-generating activities demonstrated greater financial independence and societal value. However, lack of training and awareness hinders empowerment. Traditional norms perpetuate discrimination and limit women’s opportunities to achieve freedom and equal status. This study emphasizes the need for structural and cultural reforms, including educational initiatives, occupational training, and societal acceptance of women’s roles. Policy interventions are essential to address systemic inequalities and foster an environment where women can realize their potential within families and society. South Asian J. Agric. Vol. 12, No. 1, Jun., 2026: 28-43